Profitabilitas Perbankan Dilihat dari Aspek Dana Pihak Ketiga, Kecukupan Modal dan Risiko Kredit - Riri Mayliza; Fitri Yeni; Lola Fitria Sari (JURNAL PUNDI, 2018)
Banking is a financial institution that has an important role in the economic system in Indonesia. Economic development cannot be separated from the banking sector and various factors that can influence it. This study aims to examine the effect of third-party funds, capital adequacy and credit risk toward bank profitability. The sample used in this study are banking companies listed on the Indonesia Stock Exchange and not experiencing delisting during the 2013 to 2015 observation period. Based on the results of multiple linear regression analysis it can be concluded that third-party funds and capital adequacy partially have a positive and significant impact on profitability. Meanwhile, credit risk partially has a negative and significant effect on profitability